Centralised versus decentralised administrative resource allocation in the Faculty of the Humanities at the University of the Free State - Coetsee, Marica (University of the Free State, 2015)
At present, universities find themselves in an environment of increasing competition for scarce resources in the public sector at large. Being in a competitive environment, universities might lean towards a centralised management control system (on the one extreme) to improve coordination, monitor quality and reduce costs, but still allowing academic decision-making to take place at departmental level (decentralised on the other extreme). Due to the increasing tension between these polarities, universities tend to opt for a more hybrid option by adapting the best of both practices in order to optimise the allocation of scarce resources. Furthermore, external audits and quality control mechanisms increase the accountability on the universities’ side, forcing them to implement transparent resource allocation procedures. The problem facing Faculties of the Humanities is the ability to identify the best form of an administrative framework in order to optimise resource allocation and improve service delivery in academic administration. The primary objective of this study is to propose an administrative framework for Faculties of the Humanities in order to improve service delivery in academic administration. Various qualitative research methods were used to gather data. These included the investigation of possible administrative structures available to the Faculty of the Humanities at the UFS by comparing it to the administrative structures of Humanities faculties at other universities. The recent restructuring of academic support structures in the office of the Dean in the Faculty of the Humanities at the UFS will also be analysed in an attempt to identify further optimisation of service delivery to students. Data collection took place through semi-structured interviews; informal interviews; focus-group observation and texts and electronic resources. Through process and activity analysis, the recent restructuring of academic administrative processes in the Dean’s Office in the Faculty of the Humanities was used as a basis for possible adjustments and improvements in order to identify the optimal administrative structure. Demographic change; rapid advance of digital technology; political atmosphere, and the professionalisation of university administration are all factors forcing the university and the Faculty, to adapt in order to provide their students with the best possible service. Within the Faculty, the challenge of adequate human resources is complicated further with the constant underlying tension of costs incurred for administrative staff versus academic staff. In conclusion, it is advised that the Faculty of the Humanities at the UFS adopt a hybrid administrative framework, capitalising on the strengths of both the centralised and the decentralised models. On a central level, clear guidelines through policies and procedures will provide a solid framework as reference for the Faculty to build its processes around. In turn, this will provide the Faculty with the necessary room for flexibility on a decentralised platform to make its own decisions and to respond more promptly to any external changes that might have an impact on the Faculty. Through a hybrid administrative system, collaboration between the Faculty and the central administration will be emphasised and the isolation of any of the two units from the institutional goals will be prevented.
Dissertation (MBA (Business Administration))--University of the Free State, 2015
Keywords: Resources; Centralized management; Decentralised management; Hybrid; Administrative framework; Academic administration; Qualitative research methods; Semi-structured interviews; Focus-group observation; University administration